Sweet's syndrome associated with cellulitis - a challenging diagnosis - Cristina Resende; Rui Santos; Teresa Pereira; Celeste Brito (Sociedade Brasileira de Dermatologia, 2016)
Abstract Sweet's syndrome is a neutrophilic dermatosis with worldwide distribution that has been associated with inflammatory autoimmune diseases, infections, malignancies, drugs, and pregnancy. The disease is idiopathic in up to 50% of patients. A 64-year-old woman, diagnosed with right limb cellulitis (4 days of evolution), was seen at our department, due to persistent cellulitis and progressive appearance of painful nodules and plaques in both shins and the right forearm (2 days of evolution). Taken together, clinical, laboratory and pathological data suggested the diagnosis of Sweet's syndrome, probably secondary to cellulitis of the right inferior limb. We suggest that cellulitis may be associated with Sweet's syndrome, a rare association in the literature.